Investigation of possible rickettsial infection in patients with malaria - Tay, Sun Tee; Kho, Kai Ling; Vythilingam, Indra; Ooi, Choo Huck; Lau, Yee Ling (Malaysian Society of Parasitology and Tropical Medicine, 2019)
Rickettsioses are a common health problem in many geographical areas, including rural areas in Southeast Asia. Co-infection of rickettsioses and malaria has been reported in Africa, where common reservoir and vectors are available. In this study, blood samples of Malaysian patients microscopically positive (n=148) and negative (n=88) for malaria parasites (Plasmodium knowlesi, Plasmodium malariae, Plasmodium falciparum, and Plasmodium vivax) were screened for the presence of rickettsial DNA, using PCR assays targeting specific genes. A partial fragment of rickettsial ompB gene was successfully amplified and sequenced from a patient microscopically positive for Plasmodium spp. and PCR-positive for P. vivax. BLAST analysis of the ompB sequence demonstrated the highest sequence similarity (99.7% similarity, 408/409nt) with Rickettsia sp. RF2125 (Genbank accession no. JX183538) and 91.4% (374/409 nt) similarity with Rickettsia felis URRWXCal2 (Genbank accession no. CP000053). This study reports rickettsial infection in a malaria patient for the first time in the Southeast Asia region. © 2019, Malaysian Society for Parasitology. All rights reserved.